Are men getting more emotional? Critical sociological perspectives on men, masculinities and emotions - de Boise, Sam; Hearn, Jeff (The Sociological Review, 2017)
Sociological research, influenced by feminist and other critical perspectives, has noted how men’s emotional inexpressiveness was influenced, and supported, by patriarchal privilege. Such approaches have argued that ‘inexpression’ needs to be broken down in order to build gender equality and improve men’s own wellbeing. Emerging research has, however, challenged the argument that men are ‘emotionally inexpressive’ on two main premises: that, as a result of feminist critiques, many men now practise ‘softer’ or ‘more emotional’ forms of masculinity; second, that emotions always influence social action and so need to be better incorporated into sociological accounts of men’s behaviour. Yet these approaches entail some conceptual confusion as to what emotions are, how they link to social action and whether men’s emotions are inherently transformative for gender relations. This article first details how emotions and masculinity have been theorized in feminist-inspired approaches. It outlines recent work on emotions, men and masculinities before arguing for an understanding of emotions that engages with both physiologically grounded and postconstructionist debates. It finally suggests incorporating a material-discursive approach to men’s emotions, through feminist work on affect, which is attentive to the political dimensions of ‘increasing emotionality’ in order to contribute to a developing field of sociological research.
Keywords: approches et analyses; discipline; genre; inégalités; masculinité; privilèges; rapports sociaux de sexe; ressource en ligne; sciences humaines; sociologie; systèmes d'oppressions; émotions